Evaluation of association between Parafunctional Habits and Temporomandibular Joint Disorders among dental patients - VAISHALI. S,; KUMAR M P, SANTHOSH; DURAISAMY, REVATHI (The journal of contemporary issues in business and government, 2020)
Temporomandibular disorders (TMD) are degenerative, musculoskeletal conditions associated with morphological and functional deformities. The etiology of TMD is considered multifactorial in nature and has been related to trauma, malocclusion, parafunctional habits such as bruxism, nail-biting, and non-nutritional sucking. The occurrence of TMD associated with parafunctional habits is in the ratio of women to men in 4:1. The aim of the study was to evaluate the association between parafunctional habits and temporomandibular disorders among dental patients. In this retrospective study, 51 patients with TMD as cases and 51 patients without TMD as controls were included in the study. Presence of parafunctional habits like thumb sucking, tongue thrusting, nail biting, lip biting and mouth breathing were assessed in both the groups using case sheets. Demographic details like age, gender were recorded. Excel tabulation and SPSS version 23 was used for statistical analysis. Descriptive statistics was done to describe the age and gender of the study population and they were expressed in frequency and percentage. Chi-square t test was used to test the associations between parafunctional habits and TMD; age and parafunctional habits; gender and parafunctional habits and results obtained. In this study, of 102 patients, 54.90% were males and 45.10% were females and the 21-30 years age group had a maximum number of participants (50.98%). TMD was predominantly present (29.41%) in patients with parafunctional habits than in patients without parafunctional habits (22.55%) and the results were statistically significant. (p = 0.001). The association between age and parafunctional habits was statistically not significant (p>0.05). The association between gender and parafunctional habits was statistically not significant (p>0.05). Within the limits of the study, it is evident that there is a strong association between parafunctional habits and Temporomandibular disorders among the dental patients. Thus parafunctional habits can be considered as a risk factor for TMD. It was also observed that there was no significant association of age and gender of the patients with parafunctional habits.